Implementasi Program CSR "One Village One Product: Budidaya Ikan Air Tawar" dalam Membangun Reputasi Perusahaan - Nabila Luthfiyah Basudewa; Permatasari, Andalusia Neneng (Bandung Conference Series: Public Relations, 2024)
Abstract. Corporate Social Responsibility (CSR) programs such as "One Village One Product: Freshwater Fish Cultivation" are the main strategy for the company PT. Mifa Bersaudara in order to build a sustainable reputation. Companies do not only operate to make a profit, but also pay attention to the interests of society and preserve the environment. This is proven by one of PT's PPM (Community Development and Empowerment) programs. Mifa Brothers, the PPM Program is a form of CSR from the company PT. Mifa Brothers. This program is a form of responsibility towards consumers, employees, shareholders and the environment in all aspects of company operations such as issues that impact the environment such as pollution, waste, product and labor safety. The aim of this research is to obtain information regarding socialization and how to build interaction with the One Village One Product CSR program, as well as to find out the reasons for creating the reputation of the PT company. Mifa Bersaudara through the One Village One Product CSR program. The research method used is qualitative with a case study approach. The results of this research are PT. Mifa Brothers carries out a CSR program that focuses on cultivating freshwater fish in Ujong Drien Village. The company communicates and collaborates with local communities and several agencies. The company also listens to input from the community and provides practical training. This program not only strengthens relations but also paves the way for continued mutual progress. PT. Mifa Brothers shows a strong commitment to sustainability and corporate social responsibility, which is proven by their achievements in awards events. This helps enhance their reputation as agents of change who care about the well-being of society. Abstrak. Program Corporate Social Responsibility (CSR) seperti “One Village One Product: Budidaya Ikan Air Tawar” menjadi strategi utama bagi perusahaan PT. Mifa Bersaudara dalam membangun reputasi yang berkelanjutan. Perusahaan tidak hanya beroperasi untuk meraih keuntungan saja, tetapi juga memperhatikan kepentingan masyarakat dan melestarikan lingkungan. Dibuktikan dari salah satu program PPM (Pengembangan dan Pemberdayaan Masyarakat) PT. Mifa Bersaudara, Program PPM merupakan bentuk CSR dari perusahaan PT. Mifa Bersaudara. Program ini adalah sebuah bentuk tanggung jawab terhadap konsumen, karyawan, pemegang saham, dan lingkungan dalam segala aspek operasional perusahaan seperti masalah-masalah yang berdampak pada lingkungan seperti polusi, limbah, keamanan produk dan tenaga kerja. Tujuan penelitian ini adalah untuk mendapatkan informasi mengenai sosialisasi dan cara membangun interaksi program CSR One Village One Product, serta untuk mengetahui alasan terciptanya reputasi perusahaan PT. Mifa Bersaudara melalui program CSR One Village One Product. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan studi kasus. Hasil dari penelitian ini adalah PT. Mifa Bersaudara melakukan program CSR yang berfokus pada budidaya ikan air tawar di Desa Ujong Drien. Perusahaan berkomunikasi dan bekerjasama dengan masyarakat setempat dan beberapa instansi. Perusahaan juga mendengarkan masukan dari masyarakat dan memberikan pelatihan praktis. Program ini tidak hanya memperkuat hubungan tetapi juga membuka jalan bagi kemajuan bersama yang berkelanjutan. PT. Mifa Bersaudara menunjukkan komitmen kuat terhadap keberlanjutan dan tanggung jawab sosial perusahaan, yang terbukti dengan prestasi mereka dalam ajang penghargaan. Ini membantu meningkatkan reputasi mereka sebagai agen perubahan yang peduli terhadap kesejahteraan Masyarakat.